Bangladesh environment : facing the 21st century - Gain, Philip; Moral, Shishir; Raj, Priscilla; Sircar, Lucille; Society for Environment and Human Development (Dhaka, Bangladesh) (Dhaka : Society for Environment and Human Development, 2002)
Contributed articles.
Includes bibliographical references.
BIED, ESS
Keywords: Environmental policy -- Bangladesh; Human ecology -- Bangladesh; Economic development -- Environmental aspects -- Bangladesh; Economics